(a) Differentiate each of the components to get r'(t). The rule is
.. d/dt (a*e^(bt)) = a*b*e^(bt)
The answer you have shown is the correct one.
(b) See the figure. The red curve is the position r(t) for 0 ≤ t ≤ 2. The dashed orange line is the tangent line, whose equation is
.. L(t) = r(0) +r'(0)*t = (2 +2t)i +(3 -3t)j
Answer:
ez so eu9ofjewoifjewiofjweiojfwoi
wofijwpfejwpfkjep
fre
g
wefwefw
few
f
ewgw
gwe
f
w
gewgew
f
e
w
+F
ff
qwqw
as
c+fs
afw
f
we
gw
ef
wef
sa
+fwf
as
d
wa
sf
f
a
wf
wa=d
wasd
3=
= 2412512.1.4.21.5421.3.12.542.3.215.42.4.2143.51.3
Step-by-step explanation:
9514 1404 393
Answer:
3
Step-by-step explanation:
For f(x) = x^3 -2x^2 -7x +5 and x=1/(2-√3), we have ...
f(x) = ((x -2)x -7)x +5
and ...
x = 1/(2-√3) = (2+√3)/(2^2 -3) = 2+√3
Then ...
f(2+√3) = ((2 +√3 -2)(2 +√3) -7)(2 +√3) +5
= (3+2√3 -7)(2+√3) +5
= 2(√3 -2)(√3 +2) +5 = 2(3 -4) +5 = -2 +5
f(1/(2 -√3)) = 3
_____
If you really mean x = (1/2) -√3, then f(x) = (42√3 -3)/8.
This is all I got sorry if it don’t help